PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF UNTUK MENINGKATKAN HASIL BELAJARA SISWA DALAM PEMBELAJARAN SENI RUPA DI KELAS VIII-5 SMPN 20 PADANG - NOVITA SARI, Drs. Yusron Wikarya, M.Pd. Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2016)
The purposes of this research is to increase out the field the study of student, by strategy assembling productive creative in the lesson of from art in class VIII-5 state SMP 20 of Padang. the kind of this research is research of class action (PTK) by a vesearch subject, the student class VIII-5 state SMP 20 of Padang amaunt 32 people. The instrument of collecting data at this research are student format activity, teacher format activity and the study field of evaluation sheet. The field of the research show the increase of student activity study at cycle I 62,8% be 84,34% at cycle II. Meanwhile the field of passing student study at cycle I (71,87%) increase be (100%) at cycle II.Kata kunci : Strategi Kreatif-Produktif, Hasil Belajar, Seni Rupa